Students' Thinking Processes in Solving Math Story Problems Based on the Polya Solving Model in View of Field Dependent and Field Independent Cognitive Styles in Class VII Students of MTsPN 4 Medan - Cindy Widahyu; Zul Amry (Formosa Journal of Multidisciplinary Research, 2022)
This study aims to describe students' thinking processes in solving math word problems based on the polya solving model in terms of field dependent and field independent cognitive styles. This study uses descriptive research with a qualitative approach while the data collection technique used is the GEFT test, written test questions, interviews and documentation. Subjects in this study were students of class VII MTsPN 4 Medan as many as 8 students consisting of 4 students with a field dependent cognitive style and 4 students with a field independent cognitive style. Data were analyzed with the Miles and Huberman analysis model. The results of this study indicate that the thinking processes of students with a field dependent cognitive style type tend to be computational and the thinking processes of students with a field independent cognitive style type tend to be conceptual.